International relations theories discipline and diversity - Dunne, Timothy 1965-; Kurki, Milja; Smith, Steve 1952- (Oxford University Press, 2016)
Written by the most influential scholars in International Relations, the fourth edition of this bestselling textbook provides a lively introduction to all the major theories of International Relations and draws on case studies to show how theory can help explain the dynamics of world politics